The role of donors: how to combine sector programme support with devolution? a comment from a pracitioner to James Wunsch: decentralization, local governance and "recentralization" - Nielsen, Henrik A. (2001)
In commenting on `Decentralisation, Local Governance and `Recentralisation' in Africa' (Wunsch, 2001), this article concurs with the general thesis of Wunsch that the actual implementation as distinct from the rhetoric of decentralisation in Africa has featured lingering central retention of power and resources and that genuine local control over important services and investments remains elusive. However, there is evidence that this is not invariably the case and that donors may have decisive roles to play in encouraging local assertiveness in the medium term in providing leverage for change through budget support and technical assistance to civic education, training local councillors, monitoring local government elections and encouraging local government associations to put to the test the national commitment to genuine local governance. These roles include helping to ensure the transparency of central transfers and, as in Uganda and Malawi for example, assisting with the development of intermediary fiscal mechanisms in this regard. Learning from such promising experiences will be vital in nurturing the longer term optimism heralded by Wunsch. - Reproduced.
Keywords: Local government - Africa; Local government